Analysis of Purchasing Desicion to Softbone Milkfish at Seller Center of Special Gift in Semarang City - Wijayanto, Dian; Widowati, Lestari Lakhsmi (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2011)
At the present, people is more like a softbone milkfish. That is  push the growth of  the Pandanaran Area as the seller center of special gift from Semarang. Marketing research would be done to increase understanding of consumers characteristics and to develop business of softbone milkfish, including the factors that influenced a consumers to choose a store and to buy softbone  milkfish products. This research aims to assess the influence level of decisions factors to buy and  also to scan competition of softbone milkfish sellers  at  the Pandanaran Area in Semarang. The research proved that the image and positioning “Bandeng Juwana” is very high (the most popular) as special gift of Semarang. The most decision  factor which influenced a selection of stores was taste (28%), and then followed by texture (10%), colour (10%), price (8%), packaging (7%), and store image (7 %). “Bandeng Juwana” have strength on an aspects of physical product, especially in taste and price (reasonable price), while”Bandeng Presto” have strength on a service aspects and building design. “Bandeng Bonafid” has strength on   the speed of service. The results proved that “Bandeng Juwana” would become the first choice of consumers, both before and after the process of purchasing (repurchased order). Consumers choice index were 3.74 for “Bandeng Juwana”, 3.72 for “Bandeng Presto” and 3.35 for “Bandeng Bonafid”. Key words:softbone milkfish, consumers want index, consumers choice index